Mechanisms governing phonon scattering by topological defects in graphene nanoribbons. (16th December 2015) - Zhu, Ziming; Yang, Xiaolong; Huang, Mingyuan; He, Qingfeng; Yang, Guang; Wang, Zhao
Abstract: Understanding phonon scattering by topological defects in graphene is of particular interest for thermal management in graphene-based devices. We present a study that quantifies the roles of the different mechanisms governing defect phonon scattering by comparing the effects of ten different defect structures using molecular dynamics. Our results show that phonon scattering is mainly influenced by mass density difference, with general trends governed by the defect formation energy and typical softening behaviors in the phonon density of state. The phonon scattering cross-section is found to be far larger than that geometrically occupied by the defects. We also show that the lattice thermal conductivity can be reduced by a factor of up to ~30 in the presence of the grain boundaries formed by these defects.